2015
DOI: 10.1186/s13019-015-0276-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage bilateral thoracic surgery via a combined VATS and open approach for left central bronchogenic carcinoma with carinal invasion: report of two cases

Abstract: BackgroundSurgery for patients with left central bronchogenic carcinoma invading the carina is challenging due to the complexity of left sleeve pneumonectomy, carinal resection, and airway reconstruction and management. Here we describe a modified approach to overcome this problem.Case presentationBetween March 2011 and September 2012, two patients with left central bronchogenic carcinoma invading the carina underwent single-stage bilateral thoracic surgery via a combined approach incorporating video-assisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…They proved that SRA could help both the anesthetic and surgical procedure; the lack of an endotracheal tube, in fact, makes the trachea more flexible and allows a wider range of motion for the surgeon, along with a wider field of view; these factors lead to a global reduction of operative time. Ai et al (57) reported two cases of neoplastic invasion of left main bronchus up to the bifurcation of the upper and lower lobe, the carina and the right main bronchus treated by using a bilateral combined VATS and open approach. Firstly, they performed a right posterolateral thoracotomy to resect and anatomize trachea and the right main bronchus; subsequently, they performed a VATS left sleeve pneumonectomy trough a four-port left thoracoscopy.…”
Section: Tumors >7 CMmentioning
confidence: 99%
See 1 more Smart Citation
“…They proved that SRA could help both the anesthetic and surgical procedure; the lack of an endotracheal tube, in fact, makes the trachea more flexible and allows a wider range of motion for the surgeon, along with a wider field of view; these factors lead to a global reduction of operative time. Ai et al (57) reported two cases of neoplastic invasion of left main bronchus up to the bifurcation of the upper and lower lobe, the carina and the right main bronchus treated by using a bilateral combined VATS and open approach. Firstly, they performed a right posterolateral thoracotomy to resect and anatomize trachea and the right main bronchus; subsequently, they performed a VATS left sleeve pneumonectomy trough a four-port left thoracoscopy.…”
Section: Tumors >7 CMmentioning
confidence: 99%
“…Although no randomized trials have been performed on this topic and only few case reports have been published, all authors agree that the most important factor influencing the outcomes of such a complex thoracoscopic procedure is the Endoscopic bronchial and tracheal anastomosis methods include intermittent, continuous, and continuous mixed with intermittent sutures (58)(59)(60)(61)(62)(63)(64). When performing a thoracoscopic procedure, most of authors agree on the usefulness of a complete continuous suture starting from the posterior part of the anastomosis to the anterior one, since it offers a clear operative view (53)(54)(55)(56)(57)(65)(66)(67).…”
Section: Tumors >7 CMmentioning
confidence: 99%
“…На умовах ліцензії CC BY 4.0 Тобто проведений нами аналіз характеру післяопераційних ускладнень в обох групах (табл. 7) підтверджує вплив травматичності доступу [14] не тільки на перебіг ранового процесу, але й на частоту плевро-легеневих та функціональних ускладнень, які частіше відмічалися у хворих групи порівняння. При аналізі зв'язку частоти ускладнень з характером виконаних операцій ми встановили, що найбільша кількість ускладнень відмічалася в обох групах після плевропневмонектомії, зокрема 33,0±2,6% в основній підгрупі 3 та 47,3±3,4% у хворих підгрупи порівняння 3.1 (табл.…”
unclassified